Teachers’ Perspective Towards the Implementation of High Order Thinking Skill (HOTS) in Teaching English - Pipit Muliyah (Journal of Applied Linguistics (ALTICS), 2021)
Higher Order thinking Skills (HOTS) refers to the ability to apply knowledge, skills and values in reasoning, reflection, problem solving, decision making, innovating and creating something new. Higher order thinking skills (HOTS) is a skill that should be present in every teaching. Teaching English particularly require teachers to be skillful in planning learning activities that can inculcate thinking skills among students. This study aims to explore the perceptions of English teachers in the implementation higher order thinking skills in teaching English. This is a qualitative case study involving three science teachers who teaches in government school, private school and private tutor center respectively. Data were collected through interviews only. Data were then categorized to form themes for the study. The focus of the study was teachers’ perspective, towards HOTS, its application, assessment of HOTS and the constraints. The results show that the teachers are aware and they are applying HOTS in their teaching. However, they believe they are hindered by some constraints. Therefore, this study concluded that knowledge and competence are crucial to ensure quality the implementation of HOTS. Keywords: Teaching efficacy, Evaluation, teaching English, Thinking skill